Gender wage gap across the distribution: What is the role of within- and between-firm effects? - Ezgi Kaya (IZA Journal of Development and Migration, 2021)
This paper studies the role of within- and between-firm effects on the gender wage gap (GWG). Using linked employer-employee data for Turkey for 2006 and 2014, we show that the wage gap among comparable men and women is much wider within establishments than between establishments. Our distributional analysis shows a more pronounced gap among highly paid workers, consistent with the presence of a glass-ceiling effect. This effect, however, is more apparent within establishments than between establishments, and it is the former that drives the economy-wide glass ceiling that women face. We also find that between 2006 and 2014, the GWG in Turkey widened at all points in the wage distribution, and that this widening was more pronounced within establishments than between establishments.
Keywords: J16; J31; J71; 330; gender wage gap; within- and between-establishments; wage distribution